Optimizing Early Childhood Mental Health Through Social–Emotional Stimulation Using Educational Play Equipment (APE) - Puji Nursilah; Abdulloh Aziz Assa’diy; Selda Aras (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2026)
Early childhood mental health is a fundamental aspect that determines the quality of children’s social, emotional, and cognitive development in later stages. One of the strategies to support early childhood mental health is through the use of Educational Play Tools (APE). This study aims to analyze the optimization of early childhood mental health through social–emotional stimulation by utilizing APE. The method used in this research is a qualitative Systematic Literature Review (SLR) approach. Data were obtained from various relevant national journal articles through a systematic process of selection, evaluation, and synthesis of research findings related to the use of APE in supporting children’s social–emotional development. The results of the study indicate that: (1) social–emotional stimulation plays an important role in shaping healthy mental development in early childhood, particularly in terms of emotional regulation, empathy, and social interaction skills; (2) APE has proven effective in stimulating social skills, improving emotional regulation, strengthening empathy, and helping children cope with stress through play activities; and (3) the mechanism for optimizing mental health through APE occurs through structured learning environments, positive peer interactions, and play processes that facilitate the development of resilience, self-confidence, and problem-solving skills.